Synthesis and crystal structure of N-(5-acetyl-4-methylpyrimidin-2-yl)benzenesulfonamide - Reham A. Mohamed-Ezzat; Benson M. Kariuki; Rasha A. Azzam (Acta Crystallographica Section E: Crystallographic Communications, 2023)
N-(5-Acetyl-4-methylpyrimidin-2-yl)benzenesulfonamide, C13H13N3O3S, was sythesized and characterized by single-crystal X-ray diffraction. In the crystal, π–π interactions between the phenyl and pyrimidine groups of neighbouring molecules form molecular chains parallel to [010]. Adjacent molecular chains are linked by N—H...N hydrogen-bonding interactions between the pyrimidine and amine groups of neighbouring molecules, resulting in a three-dimensional network.